Chemical constituents of Malaysian Apis mellifera propolis - Tuan Nadrah Naim Tuan Ismail,; Siti Amrah Sulaiman,; Kannan Thirumulu Ponnuraj,; Che Nin Man,; Norul Badriah Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Propolis is a resinous material collected by honey bees from various plant sources. The chemical constituents differ depending on the source of vegetation area. To date, no study of the chemical constituents of Apis mellifera propolis from Malaysia has been reported. Thus, the aim of this study was to determine the chemical constituents of Malaysian Apis mellifera propolis. Raw propolis samples were collected from Acacia mangium apiary from northern and southern regions of Peninsular Malaysia and were extracted using 70% ethanol. Then, the ethanolic extracts were evaporated and were lyophilized to dryness. The silylated compounds were identified by gas chromatography with mass spectrometry analysis (GC-MS). The compounds were characterised by comparison with NIST02 and Wiley275 libraries. Twenty-six individual compounds were identified and β-panasinsene was identified for the first time in propolis. The main compounds identified from both southern and northern regions of Peninsular Malaysia were terpenoids. Terpenoids belong to an important class in the propolis compounds due to its valuable biological properties. The amount of terpenoids ranged from 7.19 to 11.46% indicating that although the main plant source for both regions was Acacia mangium, other shrubs and fruit orchards surrounding the two apiaries may differ which may contribute to the variations.